Phytoestrogenic extracts of Cyclopia modulate molecular targets involved in the prevention and treatment of breast cancer - Visser, Jacobus Albertus Koch (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)--Stellenbosch University, 2014.